Assessment of the application feasibility of the genetic algorithm for airports operations optimization based on the collaborative decision-making principles - G. M. Lebedev; V. B. Malygin (Научный вестник МГТУ ГА)
The article proposes a formalization methodology of the basic characteristics of the production processes of the aviation industry major components, such as airlines, airports and air traffic control authorities. This technique is not exhaustive, but it is quite suitable as the basis for the formation of the initial data for decision-making optimization under the conditions of airport operations performance and air traffic management, based on the principles of work coordination of the airports operational units. It is proposed to use a genetic algorithm as a tool for optimizing collaborative decision-making, which allows for a smaller number of iterations in real time to obtain a suboptimal solution that meets the requirements of the process participants. The mathematical model in multiplicative form is presented in making an assessment of the application feasibility of the genetic algorithm, taking into account the interests of three stakeholders. Planning the use of aircraft for the airport flight schedule based on the formalized data of the airline fleet, the capabilities of the base airport apron, as well as the restrictions of permanent and temporary nature is accepted as the original product. The article demonstrates the potential advantage of the genetic algorithm, the point of which is that within each step of a suboptimal choice of priorities instead of brute-force options limited but effective direct search of a reduced number of those options that have been chosen as the "elite" by using multiplicative form is carried out.